2019
DOI: 10.1074/jbc.ra118.004479
|View full text |Cite
|
Sign up to set email alerts
|

Oligopeptide-binding protein from nontypeable Haemophilus influenzae has ligand-specific sites to accommodate peptides and heme in the binding pocket

Abstract: by guest on July 10, 2020 http://www.jbc.org/ Downloaded from Figure 1. Crystal structure of nthiOppA in closed ligand-bound conformation. A, crystal structure of nthiOppA, colored by domain (I A , salmon; I B , wheat; II, cyan), bound to co-purified peptide in green. Inset, surface and stick representation of the co-purified peptide in substrate-binding pocket. B, cartoon representation of the ligand-bound structure of nthiOppA aligned with the open unbound ecOppA structure in gray (PDB code 3TCH), and surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 56 publications
4
28
0
Order By: Relevance
“…For HbpA, the suggested site is supported by what has been previously predicted [89] and corresponds well to a very recent study where heme was docked to HpHbpA, OppA from H. influenzae (HiOppA) and NikA from E. coli (EcNikA) [90]. In the latter study, heme was suggested to bind in a site that was distinct but close to the site for other ligands (glutathione for HpHbpA, peptide for HiOppA, and butane-1,2,4-tricarboxylate-chelated nickel for EcNikA) and the ability of bind heme and other ligands simultaneously was demonstrated using surface plasmon resonance.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…For HbpA, the suggested site is supported by what has been previously predicted [89] and corresponds well to a very recent study where heme was docked to HpHbpA, OppA from H. influenzae (HiOppA) and NikA from E. coli (EcNikA) [90]. In the latter study, heme was suggested to bind in a site that was distinct but close to the site for other ligands (glutathione for HpHbpA, peptide for HiOppA, and butane-1,2,4-tricarboxylate-chelated nickel for EcNikA) and the ability of bind heme and other ligands simultaneously was demonstrated using surface plasmon resonance.…”
Section: Resultssupporting
confidence: 89%
“…In NTHi, four Cluster C proteins with capability to bind heme have been identified: HbpA, SapA, and OppA, which bind hydrophobic oligopeptides, and NTHI0310 with an unknown canonical substrate specificity. These proteins present overlapping functionality and multisubstrate specificity [90]. This may not be exclusive to NTHi given that the E. coli Cluster C nickel SBP NikA binds heme and plays a role as a heme chaperone in the periplasm [111].…”
Section: Discussionmentioning
confidence: 99%
“…Oligopeptide and dipeptide permeases have been found to be significantly up-regulated during iron starvation in other pathogenic bacteria [12,38] and they have been implicated in metal acquisition in S. aureus [39] and E. coli [40]. Moreover, some oligopeptide-binding proteins can accommodate haeme in its binding pocket [41], hence providing a new strategy to acquire iron from the host. In addition, the oligopeptide transport ATP-binding protein OppD has been shown to be critical for survival of the avian pathogen Mycoplasma gallisepticum within the respiratory tract [42], supporting the relevance of oligopeptide permeases in mycoplasma infection.…”
Section: Discussionmentioning
confidence: 99%
“…The RdKW20 strain (an avirulent d serotype strain, devoid of capsule) was the first completely sequenced bacterial genome and has been used in many studies. It expresses many different heme/hemoprotein receptors, and there are several reports of periplasmic heme-binding proteins [59,72] A, also named HI0853 in RdKW20) was the first periplasmic heme binding protein reported in this organism [73,74]. It was identified in the Hib strain DL42 (a virulent b serotype strain) as a lipoprotein, most likely anchored in the outer leaflet of the cytoplasmic membrane.…”
Section: Ia5 Unidentified Substratementioning
confidence: 99%
“…However, model building has shown that it is possible to accomodate a heme molecule in these binding sites [72]. There is no structure of apoOppAHi.…”
Section: Ia5 Unidentified Substratementioning
confidence: 99%